Reflection-AI: exploring the challenges and opportunities of artificial intelligence in higher education - Sellnow, Deanna D. (Frontiers in Communication, 2025)
A rigorous debate is underway regarding the use of artificial intelligence (AI) in higher education. Risk perceptions regarding AI range from concerns about students using AI inappropriately and unethically to teachers and teaching assistants being replaced by AI robots. This essay situates the discussion around AI historically to mitigate such fears and propose workable strategies for integrating it into the educational experience. In other words, I place AI within the frame of other new technologies that have been introduced, scrutinized, studied, and adopted throughout history (e.g., textbooks, calculators, personal computers and word processors, Internet and online learning). Ultimately, I argue that we ought to embrace the challenges posed as opportunities to again conduct theoretically driven empirical research to inform best practices for integrating AI into teaching and assessment in ways that improve learning and the environment for learning. By incorporating AI with integrity, teachers could be freed to do more deep teaching and to engage in more intellectually stimulating dialogue with students, each of which are designed to foster higher order critical thinking and analysis skills among students.